Facilitating Health and Education Sector Collaboration in Support of Comprehensive School Health - Bachop, Cindy (Can J Public Health, 2010)
Comprehensive school health (CSH) is embraced internationally as the most effective way of promoting the health of students and the school community. It is a framework for supporting improvements in students’ educational outcomes while addressing their well-being in a planned, holistic way. While many successful CSH initiatives are brought about by passionate individuals at the grassroots level, these initiatives benefit greatly from effective cross-sector collaborations within and among governments to coordinate policy and funding from the health and education sectors. Governments represent just one group of professionals within the myriad of players involved in implementing CSH in Canada. To be effective contributors to the model, all levels of government need to work together to reduce duplication while at the same time minimizing gaps in the policies and practices that support school health promotion. Collaboration between the health and education sectors within and across governmental boundaries is proving to be an effective mechanism for achieving this. In its first five-year mandate, the Pan Canadian Joint Consortium for School Health has broken new ground in horizontal integration and, as a result, has identified a set of key factors necessary for successful cross-sector collaboration. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405620 and is accessible for authorized users.